1995
DOI: 10.1164/ajrccm.152.3.7663787
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of pulmonary aspergillosis. Granulocytopenia versus cyclosporine and methylprednisolone-induced immunosuppression.

Abstract: Patients with chemotherapy-induced granulocytopenia for neoplastic diseases and those receiving cyclosporin A plus corticosteroids for prevention and treatment of organ transplant rejection are two immunologically distinct patient populations with high risks for development of invasive pulmonary aspergillosis. In order to compare the pathogenesis of aspergillosis in these two high-risk populations and to further characterize the role of cyclosporin A in development of pulmonary aspergillosis, we studied the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
1
7

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(105 citation statements)
references
References 20 publications
5
92
1
7
Order By: Relevance
“…In the former, the immune response is characterised by an important influx of neutrophils into the lung parenchyma and interleukin-10 production [59]; histological analyses demonstrate large foci of pneumonia, exudative bronchiolitis with bronchial and alveolar destructions, and haemorrhagic necrosis with neutrophil infiltration. In contrast, only a few Aspergillus are observed and are mostly in their nongerminated form when present [59,69]. Thus, in comparison with neutropenic animals, steroid-treated animals seem to die from an excessive host response rather than from a fungal invasion.…”
Section: Pathophysiologymentioning
confidence: 96%
“…In the former, the immune response is characterised by an important influx of neutrophils into the lung parenchyma and interleukin-10 production [59]; histological analyses demonstrate large foci of pneumonia, exudative bronchiolitis with bronchial and alveolar destructions, and haemorrhagic necrosis with neutrophil infiltration. In contrast, only a few Aspergillus are observed and are mostly in their nongerminated form when present [59,69]. Thus, in comparison with neutropenic animals, steroid-treated animals seem to die from an excessive host response rather than from a fungal invasion.…”
Section: Pathophysiologymentioning
confidence: 96%
“…Similar necrosis without neutrophil infiltration was seen in the infected mesenteric lymph node of patient 1 (Supplemental Figure 4). Because aspergillosis in nonneutropenic mice and humans is accompanied by robust neutrophilic tissue accumulation (28,30,31), the lack of tissue neutrophil infiltration in CARD9 deficiency despite normal peripheral neutrophil numbers represents a suboptimal innate immune response and is consistent with a defect in neutrophil recruitment from the blood into the Aspergillus-infected tissue.…”
Section: Card9 Deficiency Is Associated With Impaired Neutrophil Accumentioning
confidence: 99%
“…For example, a study showed a 100% mortality rate in granulocytopenic rabbits given ara-C but a 100% survival rate in those given CsA and methylprednisolone. 90 In another, A. fumigatus model, survival rates were significantly higher and survival durations were significantly longer in mice receiving low-dose (1 mg/ kg/day) intravenous tacrolimus but not CsA. Also, researchers observed numerous Aspergillus hyphae in the brains and kidneys of CsA-treated mice but no hyphae in the brains of tacrolimustreated animals; it is unclear if these observations are directly related to an in vitro drug effect and/or from effects on the host…”
Section: Hsp90 Inhibitorsmentioning
confidence: 99%